Sal Heartwood Borer Hoplocerambyx spinicornis Newm. (coleoptera: Cerambycidae) and its Management - Bhandari, R. S.; Rawat, J.K. (Indian Forester, 2001)
Sal heartwood borer, Hoplocerambyx spinicornis, is one of the serious insect problem in Sal forest. Outbreak this insect occur periodically in various parts of the country and may kill thousand of trees. In the present study, a short account of the life-history of Sal heartwood borer, its detection, causes of outbreak, nature of damage and past history of outbreak, nature of damage and categorisation of attacked trees is given. Practical methods for its management both preventive and remedial are discussed, including trap tree operation and removal of attacked trees.